Removal of Pb and Zn from industrial effluent using humic acid (Bangladesh Journal of Scientific and Industrial Research, 2016)
The present work was conducted to remove Pb and Zn from industrial effluents by coagulating the ions with humic acids. Seven types of effluents were collected from textile, tannery and pharmaceutical industries. Two commercially available humic acids one in a liquid state and another one in a semi-solid state, humic acid extracted from peat were used to remove Pb and Zn from industrial effluents as well as synthetic waste water. Optical property, carbon concentration and coagulation threshold of humic acids were studied. Same carbon concentration (1 x 10-5 g L-1) of all the sources was maintained at neutral pH. The values of water soluble Pb and Zn in effluents were 0.000 - 0.0711 ?g/mL and 0.002 - 0.024 ?g/mL, respectively. Results indicated that liquid humic acid having E4: E6 ratio of 1.2 removed 100% Pb and Zn only from pharmaceutical effluent whereas humic acid extracted from peat having E4: E6 ratio of 3.18 completely (100%) removed these metals from pharmaceutical and tannery effluents. Semi-solid humic acid having the lowest E4: E6 ratio of 1.07 did not form coagulation with the metals. The performance of humic acid extracted from peat was better than that of commercially available humic acids. Bangladesh J. Sci. Ind. Res. 51(4), 279-284, 2016